Genotypes of glycoprotein B gene among the Indian symptomatic neonates with congenital CMV infection - Agniswar Sarkar; Dipanwita Das; Sabbir Ansari; Rajendra Prasad Chatterjee; Lopamudra Mishra; Biswanath Basu; Sanat Kumar Ghosh; Mala Bhattacharyay; Nilanjan Chakraborty (BMC, 2019)
Abstract Background Cytomegalovirus [CMV] is a causative agent of congenital infection worldwide and often leads to neurological deficits and hearing loss in newborns. Infants born with symptomatic congenital Cytomegalovirus infection [cCMV] are at significant high risk for developing adverse long-term outcomes. In this study, we look into the sequence variability of surface glycoprotein B [gB] encoding region in newborns with symptomatic CMV infection for the first time in Eastern region of India. Methods 576 suspected newborns from seropositive mothers were subjected to the study and ELISA was used to confirm CMV infection. Different genotypes and their subtypes were determined using multiplex nested-PCR. Viral load of different glycoprotein B [gB] genotypes was measured using RT-PCR. Sequencing and phylogenetic analysis was then performed using Bayesian interference. Results The overall frequency of cCMV infection was 18.4%, where 16.0% neonates were symptomatic. Among the different gB genotypes, gB1 had the highest frequency [23.5%] and gB4 showed the lowest occurrence [5.8%]. 23.5% of symptomatic neonates had mixed genotypes of gB, probably indicating matrenal reinfection with CMV strains in Indian population. Significant genotypic clades [gB1-gB2-gB3-gB5] were grouped closely based on gene sequences, but the gB4 sequence was in the outlier region of the phylogenetic tree indicating the genetic polymorphism. Conclusion This is the first study on cCMV genotyping and its phylogenetic analysis from Eastern Indian neonatal population. The study holds importance in the assessment of cCMV seroprevalence in global perspective. gB protein can be used as a potential therapeutic target against CMV infection.